The pediatric eye exam quick reference guide office and emergency room procedures - Zhu-Tam, Lily, 1978-; Chung, Ida, 1967- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2022)
"This reference book is a clinical procedure book that provides step-by-step pediatric eye care examination techniques and will serve as a great learning and teaching tool for all eye care professionals"--